(untitled) (Vietnam Journal of Community Medicine, 2024)
Background: Cerebral circulatory insufficiency is most commonly seen in the elderly. Astragalus tonifying blood decoction combined with massage and accupressure contribute effectiveness in treatment, but it needs to be proven by research. Aim: Evaluating the effects of the formula “Huang qi bu xue tang” combined with massage and acupressure on patients with chronic cerebral circulatory insufficiency were treated at traditional medicine hospital of thai binh province in 2023. Objectives and method: Prospective, controlled trial study, comparing pre and post treatment in 60 patients randomly devided into 2 groups. Trial group: 30 patients (one Astragalus tonifying blood decoction/day + massage and accupressure), control group: 30 patients (Piracetam 400mg 3 tablets/day + massage and accupressure) in 15 days. Assessement criteria: Khadjev, VAS, Wechsler, Schulter scores, heat beat, body temperature, blood pressure. Results: The functional and physical symptoms in trial group were superior than those of control group (p<0,05). In trial group, VAS decreased (p<0,05), Wechsler’s vision and memory score increased (p<0,05), Schulter’s concerntration and motion increased (p<0,05), Khadjev score decreased (p<0,05) after treatment. No side effect was reported. Conclusion: Astragalus tonifying blood decoction combined with massage and accupressure effective improve functional and physical symptoms in chronic cerebral circulatory insufficiency.